FORMULASI DAN EVALUASI SEDIAAN LOSION DARI PERASAN BUAH BELIMBING MANIS (Averrhoa carambola L) SEBAGAI ANTIOKSIDAN - Athaillah Athaillah; Aisyah Maharani Hutauruk (Universitas Haji Sumatera Utara, 2022)
Sweet star fruits (Averrhoa carambola L) has alot of contents such as vitamin A, Potassium, fiber and vitamin C as antioxidants. Sweet star fruits juice can be made as a pharmaceutical preperation in the form of a lotion. the purpose of the study was to determine the optimum concentrastion of sweet star fruit juice on the pysical propertise of the lotion on to determine the antioxidant activity of the prearation of sweet star fruit juice. This research is an experimental study with the stages of determining vitamin C levels of sweet star fruit by iodomentric titration method before making lotion. Making lotion with 5 variations of concentration of sweet star fruit juice 15,20,25,30,35% and tested for physical stability of preparation with cycling test method as many as 6 cycling for observations were carried out each cycling which included pH and dispersion of the preparation. The results of determination of vitamin C levels in the juice of sweet star fruit are 1,232 mg/ml. The results showed that the concentration of sweet star fruit juice had no effect on the physical characteristics of the lotion preparation. Sweet star fruit juice lotion has antioxidants activity with an value of 78,797 ppm, with a strong category snd a comparison of vitamin C has value of 3,238 ppm very strong category. The concentration of sweet star fruit juice (Averrhoa carambola L) has no effect on the physical properties of sweet star fruit lotion preparation which include organoleptic, homogeneity, pH, and type of emulsion, except for the dispersion measurement for the cycling test, there is an increase in the spread area but remains stable at low temperatures and antioxidant activity in the preparation of sweet star fruit lotion in formula 4 with the best lotion texture having antioxidant activity with an value of 78,797 ppm in the strong category and in comparison vitamin C has antioxidant activity with an value of 3,238 ppm in the very strong category.